An algorithm for mapping burnt areas in Australia using SPOT-VEGETATION data - Stroppiana, D.; Tansey, K.; Gregoire, J.-M.; Pereira, J.M.C. (IEEE transactions on geoscience and remote sensing, 2003)
An algorithm has been developed to map burnt areas over the Australian continent using SPOT-VEGETATION (VGT) S1 satellite images. The algorithm is composed of a set of thresholds applied to each pixel's value of the VGT spectral channels, two spectral indices and their temporal difference. The threshold values have been derived by means of a supervised classification methodology based on the classification and regression trees algorithm. A procedure has also been developed specifically for preprocessing the daily S1 images for burnt area mapping purposes. The final product is composed of ten-day and monthly burnt area maps over Australia for the full year 2000.